THE EFFECTIVENESS OF YOGA ON QUALITY OF LIFE AND PSYCHOLOGICAL WELL-BEING IN ANXIETY DISORDERS - Deepak Kumar Kaushik, Md.Sayeeduddin, Dinesh Yadav and Komal (International journal of economic perspectives, 2021)
The benefits of Yoga are not restricted to spiritual well-being but also have physical and psychological benefits. This paper will look at the impact of yoga on psychological well being. The present study was undertaken on 100 subjects to evaluate effectiveness of Yoga therapy on Psychological well-being and Quality of life in Anxiety disorders (Generalized Anxiety disorder and stress) mild to moderate categories, diagnosed according to Dass-21 questionnaires, aged between 20 to 25 years, under medication, from Universities of Haryana to yoga department, who were willing to participate in the program were recruited. The study shows that there is significant decrease in anxiety and depression symptoms, also significant improvement in psychological well-being in players suffering from anxiety disorders with mild and moderate categories, indicating that yoga therapy with medication is significantly effective on Quality-of-life and Psychological well-being in anxiety disorders.